Pengembangan Spiritualitas Melalui Berbagi Pengalaman di Dalam Komunitas Intergenerasional - Chong Lindawati (Sekolah Tinggi Teologi Aletheia, 2023)
Abstract:Sharing experiences within the intergenerational community is something valuable for spiritual development. Unfortunately, there are various obstacles to making it happen. Among them, the individualistic lifestyle dominating the nature and existence of the community tends to be ignored. Not to mention the tendency in society that separates people based on age groups or generations, where the opportunity to understand each other and share experiences between different generations is intentionally becoming less and less. A faith community or church may be the only place where all generations gather regularly. Unfortunately, society’s trend toward generational fragmentation has moved within the church. Through a practical theological approach, this paper attempts to show how empirical experience with the support of historical and biblical traditions, as well as support from psychosocial theories, including generation theory, sociocultural learning theory, developmental theory and ecological systems theory, demonstrates the significance of sharing experiences in intergenerational communities for the developmental process of a human being. Abstrak: Berbagi pengalaman di dalam komunitas intergenerasi adalah sesuatu yang berharga bagi pengembangan spiritualitas. Sayangnya ada berbagai hambatan untuk mewujudkannya. Di antaranya, gaya hidup individualistis yang telah mendominasi sehingga hakikat dan keberadaan komunitas sendiri cenderung diabaikan. Belum lagi kecenderungan di tengah masyarakat yang memisahkan manusia berdasarkan kelompok usia atau generasi, di mana kesempatan untuk saling memahami sekaligus berbagi pengalaman antargenerasi yang berbeda secara intensional menjadi makin minim. Komunitas iman atau gereja mungkin satu-satunya tempat di mana semua generasi berkumpul secara teratur. Sayangnya, tren masyarakat menuju fragmentasi generasi telah pindah ke dalam gereja. Melalui pendekatan teologi praktis, tulisan ini berupaya menunjukkan bagaimana pengalaman empiris dengan dukungan tradisi historis dan Alkitab serta dukungan dari teori psikososial termasuk teori generasi, teori pembelajaran sosiokultural, teori perkembangan dan teori sistem ekologi menunjukkan signifikansi berbagi pengalaman di dalam komunitas intergenerasi bagi proses perkembangan seorang manusia.